Chinese networks and tariff evasion - Lorenzo Rotunno; Pierre-Louis Vézina (Graduate Institute of International and Development Studies, 2010)
In this paper we combine the tariff evasion analysis of Fisman and Wei (2004) with Rauch and Trindade's (2002) study of Chinese trade networks. Chinese networks are known to act as trade catalysts by enforcing contracts and providing market information. As tariff evasion occurs outside the law, market information is scant and formal institutions inexistent, rendering networks the more important. We find robust evidence that Chinese networks, proxied by ethnic Chinese migrant populations, increase tariff evasion, i.e. the tariff semi-elasticity of Chinese missing imports. We suggest the effects takes place through matching of illicit-minded traders, identification of corrupt customs agents and enforcement of informal contracts.
Keywords: F1; K42; F1; K42; 330; tariff evasion; China; illicit trade; migrant networks; Zoll; Schmuggel; China; Korruption; Unternehmensnetzwerk; Soziale Beziehungen; Welt